(untitled) (Italian Journal of Public Health, 2004)
The issue of Legionnaires’ disease has emerged as a major public health problem, interesting not only researchers, but also managers of public and private organisations, those responsible for public health, the general population and occasionally magistrates. The cases of legionellosis are increasing as a result of improved etiological diagnostic methods, population lifestyles and characteristics which favour the presence of the responsible organism in the environment which leads to the frequent exposure and transmission of the disease to at-risk groups whose relative numbers are growing. Legionella spp is an opportunistic waterborne pathogen that finds its ideal habitat in warm-humid environments, it is able to survive in conditions unfavourable to other germs (elevated temperatures, presence of biocides, etc.) and multiply in particular ecological niches (amoebas and other protozoa, biofilm). Because of this, it frequently colonises the hot water systems of houses, hotels, campsites, sports centres, hospitals, tertiary care centres, etc., as well as air-conditioning cooling towers, evaporative condensers and places where water stagnates at temperatures of at least 20°C. From our experience,the disease is frequently contracted by inhaling aerosols from the contaminated water systems of houses or work places, but it has also been contracted during stays in holiday accommodation, from using baths/showers in sports and recreation centres and finally during hospital stays.